Attoana : Perayaan segilintir masyarakat untuk menyelesaikan hajat - Reski Annasari (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. Attoana is a community tradition in Takalar district, precisely in Je'ne hamlet, Sanrobone subdistrict, South Sulawesi province, this tradition has been passed down from generation to generation by the Je'ne hamlet community when they have a desire, as if they have a wish, they will intend to carry out the Attoana tradition if the wish is granted. This tradition lives and continues to be carried out until now, this study aims to find out the traditions that exist in the community, namely Attoana in Lagaruda village, this tradition has an important symbolic meaning for those who believe and carry out the ritual. This research is a qualitative research that uses an ethnographic approach, the method used in its preparation is the method of observing the traditions carried out in the community in the location, conducting interviews to strengthen and clarify the results of the research for the local community. the value of the ritual performed. ATTOANA is a ritual that is maintained until now in the local community which has its own meaning in society which are habits that have been carried out for a long time, this tradition is carried out when someone has an intention/desire they intend to do ATTOANA when they have an intention it works and it is done for people who believe in it without any demands that require doing it. Keywords: Attoana, Tradition, function, meaning.